Characteristics and application of gasoline injectors to SI engines by means of measured liquid fuel distributions - Wensing, Michael; Münch, Kai-Uwe; Leipertz, Alfred (SAE Technical Papers, 1997)
The spray formation of two different gasoline port fuel injectors has been studied in three stages of the mixture formation process using measured liquid fuel distributions. The injector characteristics were determined in fundamental chamber experiments providing the time dependent spray penetration and the internal structure of the spray in quiescent air by a laser light sheet technique. For the sane injectors the interaction between port flow and spray was investigated inside the port of a production engine. A strong dependence of the fuel distribution inside the port on the engine operation point was found for both injectors. This fuel distribution provides information on wall film generation and the optimum orientation of the injector inside the suction pipe. To investigate the effect of different fuel distributions inside the port on the mixture distribution in the cylinder, examinations of the fuel distribution inside the combustion chamber of a transparent research engine were carried out. Significant changes in the mixture formation process were avoided, keeping the geometry and operating conditions of the research engine close to the production engine. It is shown in the paper how different fuel sprays (and their characteristics) are affected by the intake airflow and therefore cause differences in the mixture formation process and engine emissions. © Copyright 1997 Society of Automotive Engineers, Inc.
Created from Fastlane, Scopus look-up